Logistic principles of the public passenger transport system management - Вакуленко, Катерина Євгеніївна; Доля, Віктор Констянтинович (Eastern-European Journal of Enterprise Technologies, 2014)
The analysis of basic logistic principles, which can be applied in the development and management of the route system of public passenger transport: quality control principle, total costs principle, system stability and adaptability principle is performed in the paper. The logistic principle of the system stability and adaptability, which lies in the flexibility of public passenger transport system, its maneuverability is considered. The methodology for determining the failure probability in the tramline operation, caused by the vehicle failure and taking into account the traffic jam probability on the route is given. The methodology is based on analytical probabilistic models. The obtained probability values indicate that at an increase in the failure probability of the i-th vehicle, the failure probability of the route grows much faster with raising the number of vehicles, operating on the route. In view of the trend of development and implementation of logistic principles in public passenger transportation organization, within the logistic principle of the system stability and adaptability using the given methodology in the formation or improvement of the route network provides the possibility of rapid re-routing, assigning temporary routes, prompt intervention in the transportation process in order to meet transportation needs of the population. Also, the obtained results are useful in the organization of public electric transport routes, which requires constant intense passenger flows and developed transport communications. However, it should be noted that the drawback of the methodology is that the systematicity principle of public passenger transportation is not taken into account, and the failure probability of routes of other transport modes is not considered, which is the subject of further researches.